Manajemen Sumber Daya Manusia Pengaruh Kompetensi, Kedisiplinan Dan Sistem Kerja Terhadap Peningkatan Kualitas Kerja Guru Pada Yayasan Adlin Murni - Isnaini Mega Utari; Dhita Adriani Rangkuti (Journal of Economic, Bussines and Accounting (COSTING), 2021)
The study is conducted in order to be able to understand competence, discipline, and systems of work On The Improvement Of Teacher Work Quality In Yayasan Adlin Murni. The Yayasan Adlin Murni has a vision of becoming an excelling school of morality and excellence while the mission of the Yayasan Adlin Murni is: to educate students to become conscious of god, to be concerned about the environment, to develop students who care about science and technology, and to educate underachieving and extracurricular students. In the study the author uses a quantitative research method with the sample used amounts to 75 samples. Data analysis with a double line-regression model and thus obtaining disciplinary results and work systems are affecting the quality of work in a Yayasan Adlin Murni teacher. Keywords : Competence, Discipline, Work System, and Work quality